2013
DOI: 10.1016/j.syapm.2013.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic evaluation of the genus Enterobacter based on multilocus sequence analysis (MLSA): Proposal to reclassify E. nimipressuralis and E. amnigenus into Lelliottia gen. nov. as Lelliottia nimipressuralis comb. nov. and Lelliottia amnigena comb. nov., respectively, E. gergoviae and E. pyrinus into Pluralibacter gen. nov. as Pluralibacter gergoviae comb. nov. and Pluralibacter pyrinus comb. nov., respectively, E. cowanii, E. radicincitans, E. oryzae and E. arachidis into Kosakonia gen. nov. as Kosakonia

Abstract: The taxonomy of Enterobacter has a complicated history, with several species transferred to and from this genus. Classification of strains is difficult owing to its polyphyletic nature, based on 16S rRNA gene sequences. It has been previously acknowledged that Enterobacter contains species which should be transferred to other genera. In an attempt to resolve the taxonomy of Enterobacter, MLSA based on partial sequencing of protein-encoding genes (gyrB, rpoB, infB and atpD) was performed on the type strains and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
230
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 377 publications
(245 citation statements)
references
References 46 publications
11
230
0
4
Order By: Relevance
“…Recently, Brady et al (2013) suggested that three nonpathogenic Enterobacter spp. (Enterobacter pulveris, Enterobacter helveticus and Enterobacter turicensis), originally excluded by Iversen et al (2008b), be included as members of Cronobacter, but the current biological basis for this suggestion does not support further revision of the taxon at this time.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Brady et al (2013) suggested that three nonpathogenic Enterobacter spp. (Enterobacter pulveris, Enterobacter helveticus and Enterobacter turicensis), originally excluded by Iversen et al (2008b), be included as members of Cronobacter, but the current biological basis for this suggestion does not support further revision of the taxon at this time.…”
Section: Introductionmentioning
confidence: 99%
“…To elucidate intra-and inter-generic relationships, it has been recommended to analyse more than one gene sequence, to reduce possible ambiguities caused by genetic recombination or specific selection. Multilocus sequence analysis (MLSA) of concatenated partial gyrB, rpoB, infB and atpD gene sequences has been suggested to be a valuable tool for classification of the genera and species of Enterobacteriaceae (Brady et al, 2008(Brady et al, , 2013. The phylogenetic tree based on concatenation of these four gene sequences was preferred over trees based on single gene sequences for species identification in the genus Pantoea (Brady et al, 2008).…”
mentioning
confidence: 99%
“…nov. (61) is a newly characterized Gram-negative bacillus isolated from a toothbrush holder, with taxonomy subsequently accepted by IJSEM (62). Brady et al (63) described taxonomic reclassification of Enterobacter oryzae and Enterobacter turicensis as Kosakonia oryzae comb. nov. and Cronobacter zurichensis nom.…”
Section: Potential Emerging Pathogensmentioning
confidence: 99%